Pophyry Copper Deposits: A Plate-Tectonics Based Distribution and Occurrence Model (The Australasian Institute of Mining and Metallurgy, 1987)
The distribution of p(~rphyt1 copper deposits, in time as well as place, is used to propose an occurrence model based on the genesis models of Sillitoe and Rona. A magmatic source of the metals is accepted. The characteristic metallogenic epoch and the migration of the mineralization event along an elongate metal province are explained as the result of subduction of an obliquely- oriented strip of mineral-enriched material on the oceanic plate. Two mineral-enriched trails emanate from a hot-spot source of high-intensity hydrothermal activity in an oceanic rift. Because the whole plate system moves relative to hot spots, the hydrothermal source appears to migrate along the rift, and the two trails are not parallel to transform faults, but form a broad "V" centred on the hotspot. Source loci are spaced at intervals of about 3000 km, resulting in the possible repetition of metallogenic epochs, in a subduction zone province, at about 100 m.y. intervals. The position of the mineral-enriched strip can be found graphically, given ages of a series of deposits in a province, and the plate convergence vectors. This knowledge provides an exploration tool at regional scale and, by reflection across the rift, the potential for exploration is extended across oceans. The model has implications for commodities and deposit types other than porphyry coppers.